Puccinia jabalpurensis sp. nov. on exotic weed Lagascea mollis from India - BHANU*, CHANDRA (Indian Phytopathology, 2009)
A new species of rust fungus, Puccinia jabalpurensis collected from Lagascea mollis (Asteraceae), from Central part of India is described and illustrated. This new species of Puccinia is characterized by the presence of unique combination of features viz. compact and stromatic telia, various types of teleutospores (mostly two celled, one celled mesospore often present, three celled spores very rare), usually persistent, smooth, cylindrical to flexuous and longer teleutospore pedicel.